A classical approach for the p-Laplacian in oscillating thin domains - Nakasato, Jean Carlos; Pereira, Marcone Corrêa (Topological Methods in Nonlinear Analysis, 2021)
In this work we study the asymptotic behavior of solutions to the p-Laplacian equation posed in a 2-dimensional open set which degenerates into a line segment when a positive parameter ε goes to zero (a thin domain perturbation). Also, we notice that oscillatory behavior on the upper boundary of the region is allowed. Combining methods from classic homogenization theory and monotone operators we obtain the homogenized equation proving convergence of the solutions and establishing a corrector function which guarantees strong convergence in W^1,p for 1< p< +∞.